1997
DOI: 10.1136/bjo.81.12.1050
|View full text |Cite
|
Sign up to set email alerts
|

Pulfrich's phenomenon in unilateral cataract

Abstract: Aims-To determine whether unilateral cataract causes a pathological Pulfrich's phenomenon. Methods-29 subjects with unilateral cataract and contralateral pseudophakia were assessed on their ability to perceive the Pulfrich phenomenon. Using a computer generated pendulum image, and graded neutral density filters, a series of forced choice trials were performed in which the subject was required to describe the direction of any apparent pendulum rotation. A pathological Pulfrich eVect was said to occur when appar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…Thus, as reported by Scotcher et al, 3 our findings confirm that unilateral cataract can cause PP. We found that presence of PP was correlated with level of VA in the cataractous eyes, but found no correlation between magnitude of PP and VA in this group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, as reported by Scotcher et al, 3 our findings confirm that unilateral cataract can cause PP. We found that presence of PP was correlated with level of VA in the cataractous eyes, but found no correlation between magnitude of PP and VA in this group.…”
Section: Discussionsupporting
confidence: 91%
“…[3][4][5] The PP is a three-dimensional visual stereoillusion that was first identified by Carl Pulfrich in 1922: An object moving in front of the subject's eyes in the horizontal plane seems to follow an elliptical pathway when one eye is covered with a lightattenuating filter. 6 This phenomenon is believed to be caused by a disturbance of the observer's perception due to a disparity between the latencies of the visual pathways of the two eyes.…”
Section: Introductionmentioning
confidence: 99%
“…A unilateral dilated pupil, 5 asymmetric cataract, and unilateral lens capsule thickening after cataract surgery may cause the problem owing to interocular differences in retinal luminance. 6,7 (Readers can experience the phenomenon by viewing a pendulum moving as shown in Figure 1, with a sunglass lens in front of one eye.) Table 1 summarises the symptoms caused by the Pulfrich phenomenon.…”
Section: The Pulfrich Phenomenonmentioning
confidence: 99%
“…Since then, several authors reported that patients harbouring a spontaneous Pulfrich phenomenon report having difficulties while driving [7,14,29,30,33]. Despite that, no study has ever examined the risk of driving for patients harbouring a Pulfrich phenomenon.…”
Section: Introductionmentioning
confidence: 97%